Analysis of Viscoelastoplastic Behavior of Expanded Polystyrene under Compressive Loading: Experiments and Modeling - Imad, A.; Ouâkka, A.; Dang Van, K.; Mesmacque, G. (Проблемы прочности, 2001)
The use of expanded polystyrene (EPS) in road paving, where the soil exhibits special properties (for example, compressive soil), calls for the necessity of investigating the mechanical behavior of this material. In this work, a study of the EPS compressive behavior is presented. It is divided into two parts: experimental and modeling investigations. The experimental results show that the EPS global compression behavior is characterized by three stages. Analysis of the results shows that the density of EPS plays an important role. A phenomenological mechanical model is considered in order to simulate the EPS viscoelastoplastic behavior in the case of compressive loading. A numerical analysis has been made in order to describe the mechanical behavior of the EPS material. This investigation has revealed a good correlation with the experimental results.